Baseline cardiovascular risk assessment in cancer patients scheduled to receive cardiotoxic cancer therapies: a position statement and new risk assessment tools from the Cardio‐Oncology Study Group of the Heart Failure Association of the European Society of Cardiology in collaboration with the International Cardio‐Oncology Society. (6th August 2020) - Lyon, Alexander R.; Dent, Susan; Stanway, Susannah; Earl, Helena; Brezden‐Masley, Christine; Cohen‐Solal, Alain; Tocchetti, Carlo G.; Moslehi, Javid J.; Groarke, John D.; Bergler‐Klein, Jutta; Khoo, Vincent; Tan, Li Ling; et al.
Abstract : This position statement from the Heart Failure Association of the European Society of Cardiology Cardio‐Oncology Study Group in collaboration with the International Cardio‐Oncology Society presents practical, easy‐to‐use and evidence‐based risk stratification tools for oncologists, haemato‐oncologists and cardiologists to use in their clinical practice to risk stratify oncology patients prior to receiving cancer therapies known to cause heart failure or other serious cardiovascular toxicities. Baseline risk stratification proformas are presented for oncology patients prior to receiving the following cancer therapies: anthracycline chemotherapy, HER2‐targeted therapies such as trastuzumab, vascular endothelial growth factor inhibitors, second and third generation multi‐targeted kinase inhibitors for chronic myeloid leukaemia targeting BCR‐ABL, multiple myeloma therapies (proteasome inhibitors and immunomodulatory drugs), RAF and MEK inhibitors or androgen deprivation therapies. Applying these risk stratification proformas will allow clinicians to stratify cancer patients into low, medium, high and very high risk of cardiovascular complications prior to starting treatment, with the aim of improving personalised approaches to minimise the risk of cardiovascular toxicity from cancer therapies.